Modifying effects of lactoferrin in vitro on molecular phenotype of human breast cancer cells - Chekhun, V.F.; Zalutskii, I.V.; Naleskina, L.A.; Lukianova, N.Yu.; Yalovenko, T.M.; Borikun, T.V.; Sobchenko, S.O.; Semak, I.V.; Lukashevich, V.S. (Experimental Oncology, 2015)
Aim: To assess the role of endogenous lactoferrin (LF) in the formation of the molecular phenotype of human breast cancer (BC) cell lines with varying degrees of malignancy, including cisplatin/doxorubicin resistant cell lines, and identify possible impact of exogenous LF. Materials and Methods: 5 breast cell lines of different origin — MCF-10 A, MCF-7, including doxorubicin/cisplatin resistant ones, T47D, MDA-MB-231, and MDA-MB-468. Immunocytochemistry: expression of LF, Ki-67, adhesion molecules E- and N-cadherin, CD44, CD24 rating the invasive potential of cells. Results: Expression of LF in human BC cell lines varies. It is associated with the heterogeneity of molecular profiles of cell lines in terms of adhesion. A link has been established between the level of LF expression in the resistant cell line MCF-7/CP and MCF-7/Dox, features of their molecular profile and invasive properties. Exogenous LF was shown to be capable of modifying the molecular profile and invasive properties of all the studied cell lines including resistant ones (MCF-7/CP and MCF-7/Dox). Conclusions: The sensitivity of cytostatic-resistant cell lines (MCF-7/CP and MCF-7/Dox) tends to increase under the influence of exogenous LF. It is likely that this effect is due to LF-mediated inhibition of the expression of proteins associated with drug resistance. Key Words: lactoferrin, cell lines of human breast cancer, molecular phenotype, proliferative activity, invasive potential, adhesion molecules.